2016
DOI: 10.3389/fpsyg.2016.00256
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Phenomenological and Psychopathological Features of Trichotillomania in an Italian Sample

Abstract: Trichotillomania (TTM) is still a scarcely known and often inadequately treated disorder in Italian clinical settings, despite growing evidence about its severe and disabling consequences. The current study investigated the phenomenology of TTM in Italian individuals; in addition, we sought to examine patterns of self-esteem, anxiety, depression, and OCD-related symptoms in individuals with TTM compared to healthy participants. The current study represents the first attempt to investigate the phenomenological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Hair pulling often involves one or more body areas and may take place for consecutive hours or shorter intervals that appear throughout the day. Pulling generally occurs when alone as opposed to social environments, and many studies have demonstrated that the vast majority of those suffering from trichotillomania report feelings of unattractiveness, humiliation, and low self-confidence (4).…”
Section: Introductionmentioning
confidence: 99%
“…Hair pulling often involves one or more body areas and may take place for consecutive hours or shorter intervals that appear throughout the day. Pulling generally occurs when alone as opposed to social environments, and many studies have demonstrated that the vast majority of those suffering from trichotillomania report feelings of unattractiveness, humiliation, and low self-confidence (4).…”
Section: Introductionmentioning
confidence: 99%
“…All participants were asked, ‘Over the past 12 months, have you experienced difficulties with pulling out your hair or urges to pull out your hair for non‐cosmetic purposes?’ Participants who responded affirmatively were classified as hair pulling participants, while those who responded negatively were classified as control participants. Similar procedures for sampling participants with and without non‐cosmetic hair pulling behaviours in online, student, and community settings have been utilized elsewhere (Bottesi et al ., ; Duke, Bodzin, Tavares, Geffken, & Storch, ; Duke, Keeley, Ricketts, Geffken, & Storch, ; Shusterman et al ., ). Of the 841 participants, 527 participants (62.7%) were classified as hair pulling participants.…”
Section: Methodsmentioning
confidence: 99%
“…Trichotillomania is an obsessive–compulsive related disorder characterized by irresistible urges to pull out hair, resulting in secondary alopecia and functional impairment. [ 1 ] Trichotillomania can affect any body area, although exclusive involvement of the pubic area is very infrequent. Trichotillomania is a major psychiatric disorder,[ 1 ] even though many patients may consult a dermatologist rather than a psychiatrist.…”
mentioning
confidence: 99%
“…[ 1 ] Trichotillomania can affect any body area, although exclusive involvement of the pubic area is very infrequent. Trichotillomania is a major psychiatric disorder,[ 1 ] even though many patients may consult a dermatologist rather than a psychiatrist. Here, we present the case of a young woman with trichotillomania affecting exclusively the pubic area and who showed a good response to N-acetylcysteine and behavioral therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation